Effects of concomitant high-intensity interval training and sprint interval training on exercise capacity and response to exercise- induced muscle damage in mountain bike cyclists with different training backgrounds - Hebisz, R.; Hebisz, P.; Borkowski, J.; Zaton, M. (Isokinetics and Exercise Science, 2019)
BACKGROUND: While interval training is considered an effective modality for improving performance, its effectiveness among athletes may be influenced by previous training experience. OBJECTIVE: To investigate whether differences in training background are reflected in the development of exercise capacity and level of muscle damage following a single bout of repeated maximal sprints after an 8-week intervention of high-intensity interval training (HIIT), sprint interval training (SIT), and endurance training (ET). METHODS: Three groups of male cyclists were studied: E1 (n= 10) included cyclists with a background in high-volume moderate-intensity training, E2 (n= 7) comprised cyclists with low-volume high-intensity training experience, and C (n= 7) served as a control group with an identical training background as E1. During 8-week intervention HIIT, SIT, and ET were performed by cyclists in group E1 and E2, group C performed only ET. At pre- and post-intervention, cyclists performed two exercise tests: 1) incremental testing protocol (ITP) to assess maximal oxygen uptake (VO2max) and maximal power (Pmax); and 2) sprint interval testing protocol (SITP) to determine oxygen uptake (VO)2, work, and change in creatine kinase ( CK) and myoglobin ( Mb) levels. RESULTS: After intervention, VO2max increased in E1 and E2 group although Pmax increased only in E1. During post-intervention sprint interval testing protocol, VO2 and work increased only in E1, whereas CK and Mb decreased in E1 but increased in E2. CONCLUSIONS: A history of high-volume moderate-intensity training can induce beneficial performance adaptations by reducing muscle damage and allowing greater work output. It is suggested that interval training be preceded by a longer period of high-volume training in athletes.